2016
DOI: 10.1093/mnras/stv2963
|View full text |Cite
|
Sign up to set email alerts
|

Simulated magnetic field expulsion in neutron star cores

Abstract: The study of long-term evolution of neutron star (NS) magnetic fields is key to understanding the rich diversity of NS observations, and to unifying their nature despite the different emission mechanisms and observed properties. Such studies in principle permit a deeper understanding of the most important parameters driving their apparent variety, e.g. radio pulsars, magnetars, x-ray dim isolated neutron stars, gamma-ray pulsars. We describe, for the first time, the results from self-consistent magneto-thermal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 57 publications
0
59
0
Order By: Relevance
“…While the crustal field for both configurations evolves on a time scale of ∼ 10 4 yr into hemispherically asymmetric structures, the core field remains practically unchanged over radio pulsar lifetimes. This has been recently confirmed by Elfritz et al (2016), who performed detailed core field evolution studies. In this current paper, two representatives of these different initial field configurations (which return the same polar cap field structure conducive to radio pulsar emission) are taken as an input to explore their effect on the neutron star deformation.…”
Section: Introductionmentioning
confidence: 55%
“…While the crustal field for both configurations evolves on a time scale of ∼ 10 4 yr into hemispherically asymmetric structures, the core field remains practically unchanged over radio pulsar lifetimes. This has been recently confirmed by Elfritz et al (2016), who performed detailed core field evolution studies. In this current paper, two representatives of these different initial field configurations (which return the same polar cap field structure conducive to radio pulsar emission) are taken as an input to explore their effect on the neutron star deformation.…”
Section: Introductionmentioning
confidence: 55%
“…(22)]. The vectors ν ν ν α are, in turn, expressed through various chemical potentials and the magnetic field by the formula (30). Thus,Ė B can be calculated (even without knowing the velocity U U U ), provided that these chemical potentials are determined.…”
Section: Magnetic Field Dissipationmentioning
confidence: 99%
“…Detailed calculations show that interior magnetic field does not decay appreciably until the crustal field is dissipated, i.e. about for 10 6−7 years (Jahan-Miri 2000; Elfritz et al 2016). As for field evolution in connection with the motion of vortex lines, Gügercinoglu & Alpar (2016) have shown that during creep process force exerted by a vortex line to flux tubes during successive encounters is negligible compared to buoyancy and other forces.…”
mentioning
confidence: 99%